PROEJA: da invisibilidade excludente à visibilidade cidadã - Dreyer Netto, João Santos (2012)
The dissertation “PROEJA”: da invisibilidade excludente à visibilidade cidadã” proposes to investigate the situation that involve studentes of The National Programme for Integration of Professional Education to Basic Education the modality of education for youth and adults (PROEJA), in IFET - Porto Alegre. These students are over eighteen years of age, were excluded from the convencional educational process, are prevented, by not possessing a certificate or diploma, from exercising better paid activities because of their low education and lack of adequate professional training, and by the socio-professional changes experienced by students, from the beginning to the completion of PROEJA. The main objetive of this research is to analyze the correctness and justice of this policy of social insertion through Professional education.